2019
DOI: 10.1111/nmo.13655
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of stress‐induced gastric ulcers via central oxytocin and a potential mechanism through the VTA‐NAc dopamine pathway

Abstract: Background Oxytocin (OT) plays an important role in regulating gastric function. How OT regulates stress‐induced gastric ulcers is not understood. We investigated OT's protective role in stress‐induced gastric ulcers, with a focus on OT's interaction with the ventral tegmental area (VTA) to nucleus accumbens (NAc) dopamine pathway. Methods Drugs administration into the rats brain nuclei by brain stereotaxic apparatus, to examine related changes in gastric ulcer index, pH of gastric content, and mucus secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
(123 reference statements)
0
5
0
Order By: Relevance
“…This brain circuit plays an important role in the motivation to carry out a social behavior and serves as a natural reinforcer in some mammals [ 40 ] ( Figure 1 ). There is a high density of oxytocin receptors expressed in the VTA-NAc-DA circuit which stimulates its functioning during stress [ 41 , 42 ] ( Figure 1 ).…”
Section: Social Buffering and Stressmentioning
confidence: 99%
“…This brain circuit plays an important role in the motivation to carry out a social behavior and serves as a natural reinforcer in some mammals [ 40 ] ( Figure 1 ). There is a high density of oxytocin receptors expressed in the VTA-NAc-DA circuit which stimulates its functioning during stress [ 41 , 42 ] ( Figure 1 ).…”
Section: Social Buffering and Stressmentioning
confidence: 99%
“…In addition, the role of DA, TFF, and VIP in the occurrence and development of PUD cannot be ignored. Some studies have shown that regulating DA can ameliorate gastric ulcer (Leng et al, 2019). TFF is a small molecular polypeptide secreted by gastrointestinal mucus cells.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric neurons act on gastric motility, interact with hormones, regulate HCl and bicarbonate secretion, and induce immune responses [74,76,78,79]. As an example of the interaction with hormones, oxytocin (OT) administered in the ventral tegmental area (VTA) can activate dopamine neurons in the dopamine pathway in the nucleus accumbens through OT receptors and improve the dysfunction caused by stress in the gastric mucosa, reducing the ulcer area, stimulating mucus production, and increasing gastric pH [80].…”
Section: Gastric Neuronsmentioning
confidence: 99%